Evaluating the Response of Hypofractionated Radiotherapy versus Conventional Radiotherapy with Concurrent Cisplatin in Advanced Fixed Node Head and Neck Carcinoma - Rawal, Trilok; Pulivarthi, Prathibha; Sharma, Neeti; Jakhar, Shankar Lal; Kumar, H S; Thanvi, Shubhangi (Asian Pacific Journal of Cancer Care, 2024)
Background: The evolution of radiotherapy over recent decades has reintroduced hypofractionation for many tumor sites, with outcomes similar to those of conventional fractionated radiotherapy. While the use of hypofractionation in locally advanced head and neck cancer (LAHNC) has been explored, its application remains limited to a few countries. This trial aimed to assess the safety and feasibility of moderate hypofractionated radiotherapy (HYP-RT) in combination with concomitant cisplatin (CDDP). Objectives: The objectives of this study were to evaluate the efficacy of hypofractionated radiotherapy in advanced unresectable head and neck cancer, specifically in terms of response rate. Additionally, the study aimed to assess the local and systemic toxicities associated with the hypofractionated regimen, as well as evaluate the symptomatic improvement of radiotherapy and treatment compliance. Methods: A total of 50 cases of locally advanced head and neck cancer (stage cT4b and/or N3) without any evidence of distant metastasis were included in this study. These 50 cases were randomly assigned to the study and control groups, with 25 patients in each group. The radiotherapy regimen consisted of a single fraction of 6 Gy per week, administered over a total of 6 weeks. Patients who received less than 6 weeks of treatment were excluded from the study. The total dose administered was 36 Gy in 6 fractions. All patients were treated using unilateral or bilateral portals until a dose of 24 Gy was reached, at which point off-cord planning was implemented. For patients who exhibited complete disease regression after the initial planned dose of 36 Gy, further dose escalation was offered based on tumor regression status, tolerability, and toxicity, following institutional guidelines. Partial responders received no additional treatment until the end of the treatment period. Results: Among the study and control groups, the incidence of carcinoma of the tonsil was 12% and 20%, carcinoma of the base of the tongue was 24% and 16%, and carcinoma of the larynx was 16% and 24%, respectively. Hematological toxicities (as referenced by blood hemoglobin level) and renal toxicities (as referenced by blood urea) were assessed according to WHO toxicity criteria in all cases weekly for a duration of six weeks. In the study group, 8% had no acute hematologic reactions, 56% had grade I hematologic reactions, 28% had grade II hematologic reactions, and 8% had grade III hematologic reactions. No patients experienced grade IV hematological toxicity. Similarly, in the control group, 12% had no acute hematologic reactions, 48% had grade I hematologic reactions, 36% had grade II hematologic reactions, and 4% had grade III hematologic reactions. No patients from either group developed grade II, III, or IV renal toxicity. The rate of acute renal toxicity was comparable between the study and control groups. Conclusions: HYP-RT with concomitant CDDP was found to be feasible for LAHNC, with the rate of acute toxicity comparable to that of standard concomitant chemoradiation. The use of feeding tubes was necessary for most patients during treatment. Further investigation of this treatment strategy is warranted.